LEAP-ASIA-2019: Validation of centrifuge experiments and the generalized scaling law on liquefaction-induced lateral spreading. Issue 157 (June 2022) - Tobita, Tetsuo; Ueda, Kyohei; Vargas, Ruben R.; Ichii, Koji; Okamura, Mitsu; Sjafruddin, Asri Nurani; Takemura, Jiro; Hang, Lyu; Uzuoka, Ryosuke; Iai, Susumu; Boksmati, Jad; Fusco, Alessandro; et al.
Abstract: A round-robin centrifuge model test for an identical saturated sloping deposit with various initial conditions was conducted in the framework of liquefaction experiments and analysis project (LEAP) with 10 international institutes. To pursue two main objectives: (1) the validation of the generalized scaling law (GSL); and, (2) the development of additional experimental data that fill the gaps in the previous LEAP, each institute was assigned two tests, identical in prototype scale: a model following the generalized scaling law and a model following conventional centrifuge scaling law. The test results show a significant match in the dynamic behavior of these models, which validates the applicability of the GSL under given conditions. However, in this study, a deviation is observed when the surface ground deformation becomes larger (i.e., 250 mm). The trend surface that correlates peak amplitude of input acceleration (PGAeff ), the relative density of the ground (Dr_ q c (2.0 m)), and surface lateral displacement (Ux ) is updated and confirmed with new data sets. Highlights: First attempt to try to validate the generalized scaling law in an international round-robin project. The generalized scaling law was validated when the ground deformation was small, less than 250 mm in the present study. With accurate measurements of ground stiffness taken with miniature CPT, possibility is suggested to improve the 1- g scaling law. Relationship among input PGA, relative density of the ground and lateral displacement was updated and was consistent with the previous one.